2021
DOI: 10.3390/separations8080118
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of C18 Fatty Acids in Milk by GC-MS

Abstract: The determination of C18 fatty acids (FAs) is a key and difficult aspect in FA profiling, and a qualified method with good chromatographic separation and high sensitivity, as well as easy methylation, is required. A GC-MS method was established to simultaneously determine C18 FAs in milk. To simplify the methylation protocol for milk samples, besides a base-catalyzation methylation (50 °C for 20 min), the necessity of an additional acid-catalyzation was also studied using different temperatures (60 °C, 70 °C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Previous studies reported that t 9, c 12, c 15-C18:3 has been found in the processing of food [ 5 ]. Recent studies have found that there are t 9, c 12, c 15-C18:3 in milk [ 6 ], but the concentration was low.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that t 9, c 12, c 15-C18:3 has been found in the processing of food [ 5 ]. Recent studies have found that there are t 9, c 12, c 15-C18:3 in milk [ 6 ], but the concentration was low.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of fatty acids and fatty acid methyl esters (FAMEs) from ruminal fluid was according to a previous protocol [ 6 ]. A 2 mL aliquot of each sample was transferred to a 15 mL tube and 4 mL of n-hexane/isopropanol ( v / v = 3/2) solution was used to extract the fat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimization of the sodium methoxide FAME derivatization technique. See DOI: https://doi.org/10.1039/d3ay00407d ionization detector (GC-FID) methods [3][4][5][6][7][8][9] to gas chromatography-mass spectrometry (GC-MS) methods [10][11][12][13][14][15][16][17][18][19] due to the higher sensitivity of the MS detectors, 20,21 giving a better estimate of FAs present in the analyte of interest.…”
Section: Introductionmentioning
confidence: 99%